Comprehensive Review on UAV Efficient Path Planning Techniques for Optimized Applications - Senthilkumar, T. (Journal of Ubiquitous Computing and Communication Technologies, 2022)
This literature review article compiles works that describe the use of bio-inspired algorithms in Unmanned Aerial Vehicle (UAV) motion planning. This review demonstrates the usefulness of the various frameworks by presenting the contributions and limits of each article. The optimization method also decreases the amount of inaccuracy in the system’s convergence. Furthermore, this study discusses the assessment procedures and draws attention to the novelties and limitations of the explored methods. The paper wraps up with a detailed examination of the current difficulties and potential future research directions. This research will aid scholars in comprehending the state-of-the-art efforts made in UAV motion planning using a variety of optimization strategies.